Aggregates of alternate amphiphilc polyanion to carry zwitterionic drug in aquedous media (2015)
The effect of amphiphilic polyanion Poly(maleic acid-alt-octadecene)sodium salt on solubility of a zwitterionic drug (ampicillin trihydrate) in aqueous media was evaluated. This polymeric salt was obtained by an equimolar reaction of parent copolymer poly Poly(maleic acid-alt-octadecene)with an aqueous solution of NaOH. The obtained amphiphilic polyanion was purified by dialysis and lyophilization and was characterized by FTIR spectroscopy. Secondly, a method for the model drug quantification by UV spectrophotometry at 37°C was standardized. Also the grade of association drug-polymer in aqueous media using ultrafiltration methodology at three levels of temperature (20, 30 and 40°C) and two levels of pH (1.2 and 7.4) was determined. Finally, the variation of aqueous solubility of ampicillin trihydrate in ultra-pure water and two buffer media with pH of 1.2 and 7.4 with an ionic strength of 0.15 M at 37°C in presence and absence of amphiphilic polyanion was evaluated. It was found that maximum solubility is reached at a pH value of 1.2 in absence of polymeric material with a value of 36 mg/mL, which diminishes dramatically to a value of 8.3mg/mL when the polyanion is added. In the other side, when the system has a pH value of 7.4, the drug solubility slightly increases from 13 to 16mg/mL in presence of polymeric material, describing that solubility of this kind of drugs is strongly influenced by aqueous media and this type of polymeric materials.